ESG Rating Formula for the Freight Forwarding Industry - Philip, Alex (Digital Repository of Theses - SSBM Geneva, 2024)
This study focuses on ESG rating for Freight Forwarding Industry, which is mainly an asset light industry. Freight Forwarding Industry uses Ships, Aircrafts, Trucks, Warehouses etc. owned by other companies. Currently there are various ESG rating agencies which collects data from company websites, annual reports, CSR reports / Sustainability reports, media sources, company disclosures, NGO reports, stock exchange filing, survey etc. ESG does not have a Globally Uniform Standard Reporting, which makes it confusing and difficult to compare. As of now, rating agencies use different weightage, criteria, and evaluation methods irrespective of geographical location. Further, they are mainly transaction focused and not system focused. For multinational companies which operates in many countries, country specific weightages are not considered. This study derives a new a formula for ESG rating by considering all the possible criteria, giving appropriate weightage to environment, social and governance for the respective country. The final company score will be the cumulative of, country score and business volume for the respective year. The Global ESG Score for a company will be represented as GS (Global ESG Score). GS = S ( CSi * BVi ) Global ESG Score = S (Country ESG Score * Country’s Business volume) vi The weightages used are globally accepted country specific indexes. This will help different stake holders (viz, shareholders, employees, business partners, government) of the company to have measurable, testable, and convincing SBTi with respect to ESG score. To have better clarity and understanding on the new formula, a case study with 3 years real data of an MNC has been included in this study.